Knowledge management and the power of communication: INDESGUA as a social technology enabling equitable access to scholarships in Guatemala - Bonilla, Kleinsy; Barrientos, Natalia Ortiz; Contreras, Miguel Alejandro Saquimux (Frontiers in Communication, 2025)
This community case study examines the actors, conditions and context in which scholarships offered by international cooperation programs to access higher education are managed in Guatemala. It documents a communication-based social technology initiative led by organized local civil society: the Institute for the Development of Higher Education in Guatemala—INDESGUA, a nonprofit organization founded in 2007. Using a qualitative methodology that combines in-depth and semi-structured interviews with an analysis of organizational records, this article reflects on the mediating role INDESGUA plays between individuals (demand side) seeking scholarships and providers (offer side), with specific objectives of facilitating access to traditionally excluded groups of Guatemalan society, specifically rural youth, young women, and indigenous populations. The analysis covers 2007 to 2023. The findings show that knowledge management and communication are central elements of INDESGUA’s operation and promote social inclusion. However, structural inequalities and contextual systematic biases may limit the effectiveness of these efforts.